Utilization of Colonial Buildings into Business Houses in Semarang - Hardianningrum, Ratna; Rizkia, Retno (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
Colonial buildings that still survive today are the main attraction because they have high characteristics and historical value. Colonial buildings are one of the cultural heritage that need to be maintained. The existence of colonial residential buildings must be maintained and utilized commercially as one of the solutions to survive. Maintenance of old colonial buildings is not easy, it needs to be quite expensive due to the age of the building and the need for rejuvenation. Heirs or owners of colonial buildings must maximize the building commercially, one of which is on the building on Jalan Beringin Sekayu Semarang by making it a business house. This colonial building has not yet entered the cultural heritage building. Still, it has the potential to enter the cultural heritage building in the future judging from the history and appearance of the building's façade. The use of colonial residential buildings in business houses needs careful adjustment and arrangement because of the existence of 2 different functions. Residential houses are private zones that require the privacy of homeowners and their families, while business premises are public zones that can be accessed publicly and must reflect professionalism to be trusted by clients and must increase employee productivity. Comfort as a home and professionalism in a place of business are not easy to do without good planning. Planning must not change the total face of the building so that the historical value of the cultural heritage is not lost. Spatial adjustments must also be made by considering aspects of function, comfort, and professionalism. Without good planning, colonial buildings that have historical value, and cultural heritage characteristics will be lost and buildings cannot function properly with disruption of activities as residences and places of business. The research was conducted with descriptive qualitative research methods through field observation, interviews, and literature studies. Research needs to be done so that colonial buildings can survive as cultural heritage and be used properly with adjustments due to their function as a residence as well as a place of business. The results of the study can describe the changes or adaptations that occur due to the use of colonial buildings of residential houses in places of business. These changes and adaptations include the appearance of the façade, zoning area, and circulation.